3rd Polish Optical Conference 2013 (PKO 2013) - Weinert-Rączka, Ewa; Mackowski, Sebastian (Photonics Letters of Poland, 2013)
The current issue of the Photonics Letters of Poland contains mainly selected papers that were presented during the 3rd Polish Optical Conference that was held from June 30th to July 4th, 2013 in Sandomierz, Poland. The remaining three papers included in the issue are regular contributions.